MWCNT modified glassy carbon electrode in presence of cationic surfactant for the electro-analysis of paclitaxel - Jayant I. Gowda (Elsevier, 2021)
A highly sensitive electrochemical sensor was constructed by layering a MWCNT on a glassy carbon electrode in presence of cationic surfactant, cetyltrimethyl ammonium bromide (CTAB). Surface morphology of developed sensor was carried by AFM technique and used for the electrochemical detection of an anticancer drug paclitaxel (PAC) in pure and dosage form by cyclic and differential pulse voltammetric techniques. Results showed modified sensor exhibited high specific surface area and its morphology consists of very thick and fine particles of MWCNT in presence of surfactant. Optimized the experimental condition by varying the surfactant concentration, accumulation time, buffer pH and scan rate. With standard pH of 7.0, for different scan rate variation (25 to 300 mV/s) a diffusion controlled surface phenomenon was observed on constructed sensor. Detailed electro-chemical oxidation mechanism was proposed based on the obtained result. MWCNT-CTAB/GCE provided lower detection limit and lower quantification limit of 4.38 × 10−10 M and 1.46 × 10−9 M respectively over the concentration ranges of 10.0 × 10−8 and 12.0 × 10−6 M.The MWCNT-CTAB/GCE was successfully applied for recovery of analyte in real sample and pharmaceutical sample. A good recovery percentage with lower RSD values depicts the sensitivity and selectivity of the sensor.